Benchmarking QCi's EmuCore Device for Time Series Forecasting - Babak Emami; Prajnesh Kumar; Wesley Dyk (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
Reservoir computing (RC) has emerged as an efficient and scalable approach for processing time-dependent data, particularly in physical reservoir computing implementations. QCi's EmuCore platform, a novel photonic-inspired time-delayed reservoir system, offers a compact and energy-efficient solution for dynamic data transformations. In this study, we perform a comprehensive benchmark of EmuCore using the Mackey-Glass blood cell production model, a challenging nonlinear time series forecasting task. EmuCore's performance is compared against classical reservoir computing, RNN, and LSTM models implemented on both Apple M2 CPUs and Nvidia Jetson Nano GPUs.